The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4236/ojanes.2012.23020
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Spinal Anesthesia with Levobupivacaine and Hyperbaric Bupivacaine for Cesarean Sections: A Randomized Trial

Abstract: Purpose: Levobupivacaine showed a lower risk of cardiovascular and central nervous system (CNS) toxicity than bupivacaine which is the most popular local anesthetic agent in obstetric practice. The aim of this study was to investigate the clinical efficacy of levobupivacaine compared with hyperbaric bupivacaine for spinal anesthesia for cesarean section. Methods: 60 pregnant women in ASA I -II group scheduled to have elective cesarean operation were allocated into the study. Patients were randomly divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
40
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 26 publications
14
40
1
2
Order By: Relevance
“…Our result corroborates with the finding of Demet Gulec et al, Gulen Guler et al, [8] Mantouvalou M. et al, who concluded that motor block onset time was significantly shorter in Bupivacaine gr compared to Levobupivacaine gr.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our result corroborates with the finding of Demet Gulec et al, Gulen Guler et al, [8] Mantouvalou M. et al, who concluded that motor block onset time was significantly shorter in Bupivacaine gr compared to Levobupivacaine gr.…”
Section: Discussionsupporting
confidence: 93%
“…So, their finding was similar to our finding. Similar to our study was the finding of Gulen Gular et al [8] In our study, onset time to T 10 level sensory block (mins) was significantly prolonged in Gr A compared to Gr B. In the study done by F. Erdil et al, [9] the onset time to T 10 level sensory block was significantly shorter in Bupivacaine group than in Levobupivacaine group.…”
Section: Discussionsupporting
confidence: 82%
“…These results were comparable with other studies. [1][2][3][4] In this study, time of onset of sensory analgesia up to T 6 was 12.07 ± 5.95 min and 17.52 ± 8.3 min in Group B and Group L, respectively. Onset of sensory analgesia at T 6 was slower in Group L than Group B.…”
Section: Discussionmentioning
confidence: 99%
“…[5] In this study, time for two segment regression of sensory level was 103.86 ± 23.59 min and 108.06 ± 24.92 min in Group B and Group L, respectively. In this study, time for complete regression of sensory level was 228.8 ± 40.58 min and 239.86 ± 46.8 min in Group B and [2][3][4][5] In this study, 28 out of 30 patients in both groups had Category A quality anesthesia. One patient in bupivacaine group and two in levobupivacaine group had Category C quality of anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation